Developing a constitution for Europe - Eriksen, Erik Oddvar, 1955-; Fossum, John Erik; Menéndez, Agustín José (Routledge studies on democratizing Europe, 2004)
The European Union is currently in the midst of a comprehensive process of reform and the aim of this book is to address the challenge of forging a legitimate Constitution for the EU. These authors clarify the constitutional status of the EU, to take stock of the European Charter of Fundamental Rights and Convention of the Future of Europe as vehicles to foster and create a European constitution.